Continuous monitoring of snowpack dynamics in alpine terrain by aboveground neutron sensing. Issue 5 (2nd May 2017) - Schattan, Paul; Baroni, Gabriele; Oswald, Sascha E.; Schöber, Johannes; Fey, Christine; Kormann, Christoph; Huttenlau, Matthias; Achleitner, Stefan
Abstract: The characteristics of an aboveground cosmic‐ray neutron sensor (CRNS) are evaluated for monitoring a mountain snowpack in the Austrian Alps from March 2014 to June 2016. Neutron counts were compared to continuous point‐scale snow depth (SD) and snow‐water‐equivalent (SWE) measurements from an automatic weather station with a maximum SWE of 600 mm (April 2014). Several spatially distributed Terrestrial Laser Scanning (TLS)‐based SD and SWE maps were additionally used. A strong nonlinear correlation is found for both SD and SWE. The representative footprint of the CRNS is in the range of 230–270 m. In contrast to previous studies suggesting signal saturation at around 100 mm of SWE, no complete signal saturation was observed. These results imply that CRNS could be transferred into an unprecedented method for continuous detection of spatially averaged SD and SWE for alpine snowpacks, though with sensitivity decreasing with increasing SWE. While initially different functions were found for accumulation and melting season conditions, this could be resolved by accounting for a limited measurement depth. This depth limit is in the range of 200 mm of SWE for dense snowpacks with high liquid water contents and associated snow density values around 450 kg m −3 and above. In contrast to prior studies with shallow snowpacks, interannual transferability of the results is very high regardless of presnowfall soil moisture conditions. This underlines the unexpectedly high potential of CRNS to close the gap between point‐scale measurements, hydrological models, and remote sensing of the cryosphere in alpine terrain. Key Points: First application of monitoring a mountain snowpack via cosmic‐ray neutron sensing (CRNS) High correlation with both snow depth and water equivalent obtained via Terrestrial Laser Scanning (TLS) No complete saturation of CRNS signal even for snowpacks up to 600 mm snow water equivalent